Training of teachers of the first year of primary school to implement the competency-based approach - according to teachers and inspectors - - Harkas, Wassila; Merabat, Halim; Berinat, Soufiane (Journal of Human Sciences, 2021)
This study aims to identify the reality of the process of preparing primary school teachers, and to what extent their preparation programs respond to the application of the Competency Approach according to teachers, educational and training inspectors. That approach, was adopted by the Algerian educational system, starting from the 2003/2004 academic year. To achieve this goal, we applied a questionnaire to a sample of first-year primary school teachers consisting of 343 teachers and a sample of 13 inspectors. The results obtained in our research indicated that first-year primary school teachers did not receive sufficient numbers to qualify them to apply the competency approach to the new educational curricula.